2021
DOI: 10.3389/fimmu.2021.720205
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein-Directed Monoclonal Antibodies May Ameliorate COVID-19 Complications in APECED Patients

Abstract: Patients with the monogenic immune dysregulatory syndrome autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), which is caused by loss-of-function mutations in the autoimmune regulator (AIRE) gene, uniformly carry neutralizing autoantibodies directed against type-I interferons (IFNs) and many develop autoimmune pneumonitis, both of which place them at high risk for life-threatening COVID-19 pneumonia. Bamlanivimab and etesevimab are monoclonal antibodies (mAbs) that target the SARS-CoV-2 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…This finding is most likely due to the presence of neutralizing autoantibodies directed against type-I interferons (IFNs) and preexisting autoimmune pneumonitis typical of the disease ( 71 , 72 , 75 , 79 ). Respiratory failure was the main cause of death in APECED, but early therapeutic intervention with anti-SARS-CoV-2 mAbs may be beneficial ( 80 ).…”
Section: Primary Immune Regulatory Disordersmentioning
confidence: 99%
“…This finding is most likely due to the presence of neutralizing autoantibodies directed against type-I interferons (IFNs) and preexisting autoimmune pneumonitis typical of the disease ( 71 , 72 , 75 , 79 ). Respiratory failure was the main cause of death in APECED, but early therapeutic intervention with anti-SARS-CoV-2 mAbs may be beneficial ( 80 ).…”
Section: Primary Immune Regulatory Disordersmentioning
confidence: 99%
“…In our experience with SARS-CoV-2–infected APECED patients at the NIH Clinical Center, we proceed with prophylactic hospital admission upon diagnosis for close clinical monitoring. In the early ambulatory non-hypoxemic phase of the infection, we consider administration of anti-spike SARS-CoV-2 monoclonal antibodies ( 104 ), which was shown to decrease the risk of hospitalization, severe infection, and death from COVID-19 in high-risk individuals without APECED ( 105 ). Administration of IFN-β and/or plasmapheresis could also be considered in this setting ( 84 , 106 ).…”
Section: Pathogenesis Of Aire Deficiencymentioning
confidence: 99%
“…They further suggested that the early administration of IFN-α or -β in the course of SARS-CoV-2 infection might benefit patients with inborn errors impairing the production of type I IFNs ( 22 ), whereas IFN-β administration may be beneficial in patients with neutralizing auto-Abs against IFN-α but not IFN-β ( 23 , 24 ). Moreover, these findings suggested that patients with inborn errors of the type I IFN response pathway or with auto-Abs neutralizing both IFN-α and IFN-β should be treated differently, perhaps with monoclonal antibodies (mAbs) against SARS-CoV-2 ( 25 27 ).…”
mentioning
confidence: 99%